Application of Aromatherapy Inhalation Therapy in Children with Ineffective Airway Clearance Due to Bronchopneumonia in Room Cendana 3, Kardinah Regional General Hospital, Tegal City - Rahayu, Windy; Andhini , Citra Setyo Dwi; Purbasari, Dwiyanti (INDOGENIUS, 2025)
Background & Objective: Bronchopneumonia is one of the most common forms of lower respiratory tract infections in children and often causes ineffective airway clearance due to secretions buildup. This study aims to evaluate the effectiveness of nursing interventions using aromatherapy inhalation therapy in improving airway clearance in children with bronchopneumonia. Method: Descriptive, applying the results of previous case studies, using a pediatric nursing care approach and the innovative intervention of aromatherapy inhalation therapy. Result: Significant effectiveness was demonstrated, marked by a decrease in respiratory rate from 44 breaths per minute to 32 breaths per minute, more effective coughing, and reduced rales on lung auscultation. Conclusion: Aromatherapy inhalation therapy intervention was proven to help thin secretions and facilitate mucus clearance. Therefore, this intervention can be considered an alternative supportive measure in pediatric nursing care for children with bronchopneumonia experiencing airway clearance disorders.